DEVELOPMENT OF A TOOL TO ASSESS KNOWLEDGE, ATTITUDE, AND SATISFACTION LEVEL OF PATIENTS TOWARD AYURVEDA - SUBHAJIT HAZRA; KUNDAN SINGH BORA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study primarily intended to formulate and corroborate a scale to evaluate knowledge, attitude, satisfaction, and continuation of Ayurveda practice. Methods: After a literature search, an initial questionnaire was drafted encompassing 33-items within four constructs, namely, knowledge, attitude, satisfaction, and continuation with Ayurveda. The developed questionnaire was assessed for content validity by five experts. Results: After confirmatory factor analysis, 33-items were reduced to 22-items, confirming the structure of the scale. Further, the content validity at the scale level was above the acceptable value of 0.78, suggestive of the content validity of the scale. Spearman-Brown coefficient values for knowledge, satisfaction, and continuation with Ayurveda range between 0.7 and 0.9, suggesting good reliability. In addition, the test-retest reliability value was >0.7 for knowledge, attitude, satisfaction, and continuation with Ayurveda. Cronbach’s alpha values ranging between 0.6 and 0.9 also suggest good internal consistency for the scale. Finally, the convergent (average variance extracted values) and discriminant (Fornell and Larcker) validity of the variables was met and the model indices (Chi-square 613.22; CMIN/DF<5) showed good fit. Conclusion: The formulation of an evaluation scale is described in this paper to measure knowledge, attitude, satisfaction, and continuation with Ayurveda practice. Based on the validity analysis, this questionnaire, with four variables and a total of 22-items, can be added to the present research on Ayurveda practice.